Three IgH isotypes, IgM, IgA and IgY are expressed in Gentoo penguin and zebra finch. - Binyue Han; Yan Li; Haitang Han; Yaofeng Zhao; Qingjie Pan; Liming Ren (PLoS ONE, 2017)
Previous studies on a limited number of birds suggested that the IgD-encoding gene was absent in birds. However, one of our recent studies showed that the gene was definitely expressed in the ostrich and emu. Interestingly, we also identified subclass diversification of IgM and IgY in these two birds. To better understand immunoglobulin genes in birds, in this study, we analyzed the immunoglobulin heavy chain genes in the zebra finch (Taeniopygia guttata) and Gentoo penguin (Pygoscelis papua), belonging respectively to the order Passeriformes, the most successful bird order in terms of species diversity and numbers, and Sphenisciformes, a relatively primitive avian order. Similar to the results obtained in chickens and ducks, only three genes encoding immunoglobulin heavy chain isotypes, IgM, IgA and IgY, were identified in both species. Besides, we detected a transcript encoding a short membrane-bound IgA lacking the last two CH exons in the Gentoo penguin. We did not find any evidence supporting the presence of IgD gene or subclass diversification of IgM/IgY in penguin or zebra finch. The obtained data in our study provide more insights into the immunoglobulin heavy chain genes in birds and may help to better understand the evolution of immunoglobulin genes in tetrapods.